Proyecto de factibilidad para la creación de una microempresa que ofrece servicio de licor y snacks a domicilio en el norte de la ciudad de Quito - Endara Rojas, María Fernanda (2013)
In the development of this project is to determine the feasibility of implementing a business in the north of the city. To initiate this study, an analysis of the market in which you want to enter, in the northern part of the capital is made. This chapter is the main base of the project since the supply, demand and market influence is studied. Complementing the project size analysis about demand, technology and supplies used during its development is done.